Measuring hindfoot alignment radiographically: the long axial view is more reliable than the hindfoot alignment view - Reilingh, Mikel L. (Springer-Verlag, 2010)
BACKGROUND: Hindfoot malalignment is a recognized cause of foot and ankle disability. For preoperative planning and clinical follow-up, reliable radiographic assessment of hindfoot alignment is important. The long axial radiographic view and the hindfoot alignment view are commonly used for this purpose. However, their comparative reliabilities are unknown. As hindfoot varus or valgus malalignment is most pronounced during mid-stance of gait, a unilateral weight-bearing stance, in comparison with a bilateral stance, could increase measurement reliability. The purpose of this study was to compare the intra- and interobserver reliability of hindfoot alignment measurements of both radiographic views in bilateral and unilateral stance. MATERIALS AND METHODS: A hindfoot alignment view and a long axial view were acquired from 18 healthy volunteers in bilateral and unilateral weight-bearing stances. Hindfoot alignment was defined as the angular deviation between the tibial anatomical axis and the calcaneus longitudinal axis from the radiographs. Repeat measurements of hindfoot alignment were performed by nine orthopaedic examiners. RESULTS: Measurements from the hindfoot alignment view gave intra- and interclass correlation coefficients (CCs) of 0.72 and 0.58, respectively, for bilateral stance and 0.91 and 0.49, respectively, for unilateral stance. The long axial view showed, respectively, intra- and interclass CCs of 0.93 and 0.79 for bilateral stance and 0.91 and 0.58 for unilateral stance. CONCLUSION: The long axial view is more reliable than the hindfoot alignment view or the angular measurement of hindfoot alignment. Although intra-observer reliability is good/excellent for both methods, only the long axial view leads to good interobserver reliability. A unilateral weight-bearing stance does not lead to greater reliability of measurement.